2012
DOI: 10.3233/cbm-2012-00275
|View full text |Cite
|
Sign up to set email alerts
|

Association between newly identified variant form of DNA polymerase betaΔ208–304 and ovarian cancer

Abstract: The result reveals that this variant form of polβ is a predisposing factor for stage IV ovarian cancer samples in Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Mutations in polβ may influence aggressive solid tumour phenotype and response to chemotherapy [13]. In ovarian cancers, mutations in polβ have been recognised [41] although clinical significance remains unclear [41]. In clinical cohorts of ovarian cancers, we show that low Polβ expression is associated with better PFS.…”
Section: Discussionmentioning
confidence: 75%
“…Mutations in polβ may influence aggressive solid tumour phenotype and response to chemotherapy [13]. In ovarian cancers, mutations in polβ have been recognised [41] although clinical significance remains unclear [41]. In clinical cohorts of ovarian cancers, we show that low Polβ expression is associated with better PFS.…”
Section: Discussionmentioning
confidence: 75%
“…In our previous study, we found an ovarian cancer-specific mutation in the DNA Polβ, with the deletion in the catalytic domain [ 9 ]. This mutated protein (PolβΔ) was co-expressed with wild-type Polβ in heterozygous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide sequences of the Polβ and PolβΔ were used from our previously published literature [ 9 ], provided in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in Pol β are also highly linked to lung, breast, bladder, and esophageal cancers [6]. Khana et al [7][8][9][10][11] explored various Pol β mutations associated with ovarian cancers. Ovarian cancer is a signi cant health concern among Indian women, ranking as the third most common cancer and the eighth most prevalent overall in the country.…”
Section: Introductionmentioning
confidence: 99%